Роман Ігоря Муратова «Сповідь на вершині» у контексті українського літературного процесу 1970-1980-х років - Веретюк, Т. (Літературознавчі обрії. Праці молодих учених, 2010)
The article discusses the novel «Confession on the peak» by Igor Muratov in the context of the Ukrainian literary process of 1970’s–1980’s of the XX century. It deals with the development of genre variety of biographical documentary epos. The article presents the image of the main character Vital y Prymakov not only as an imaginary person, but also as a real historic personality.